¿Cuán rentable es la educación superior en Colombia? - Gustavo Adolfo Hernández Díaz (Lecturas de Economía, 2010)
This paper examines the education premium for graduate students in Colombia, focusing on the screening hypothesis which is tested via sheepskin effects. A new dataset for higher education is constructed using administrative records of educational institutions and social security information. The findings suggest that the Colombian labor market places a high value on an individual’s alma mater, followed in, second place, by undergraduate field of study. Finally, the evidence also implies that job experience acquired after obtaining a degree has a higher return than job experience obtained before or not related to the degree’s field of study.